Trust Analysis, Service Quality on Purchase Interest, Atome Payment Moderation - Koerniawan Hidajat; Fais Datul Fidad Nurul Islam (Ilomata International Journal of Tax and Accounting, 2022)
The shopping center at Bata Sunter Mall in Jakarta experienced a decline in sales due to the Covid-19 pandemic, entering the new normal experienced a change in shopping. The aim of this approach is to fulfill consumer trust and make positive use of digital technology. The research method of this research is casual associative quantitative and the data obtained through a questionnaire. The results of this study indicate that entering the new normal is a step for consumers to shop during the pandemic. Since its implementation, physical distancing has been in the rules of the Indonesian government and its policies.